The Landless Farmworkers Movement (MST) in Brazil today: struggle, organization and education - Célia Regina Vendramini; Sonia Maria Rummert (Universidade Federal de Santa Catarina, 2009)
O movimento dos trabalhadores rurais sem terra (MST) na atualidade: luta, organização e educação